2014
DOI: 10.1017/jfm.2014.660
|View full text |Cite
|
Sign up to set email alerts
|

Organised large structure in the post-transition mixing layer. Part 2. Large-eddy simulation

Abstract: Three-dimensional large-eddy simulations of two-stream mixing layers developing spatially from laminar boundary layers are presented, replicating wind-tunnel experiments carried out in Part 1 of this study. These simulations have been continued through the mixing transition and into the fully turbulent self-similar flow beyond. In agreement with the experiments, the simulations show that the familiar mechanism of growth by vortex amalgamation is replaced at the mixing transition by a previously unrecognised me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
67
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(80 citation statements)
references
References 55 publications
13
67
0
Order By: Relevance
“…24 Whilst these studies were limited to the pre-transition region, more recent research has shown that simulation of initially laminar mixing layers with pseudorandom inflow disturbances leads to post-transition large-scale coherent structures which grow continuously and linearly throughout their lifetimes. 23 Flow visualisation of the high Reynolds number simulated flow shows that streamwise vorticity develops in the mixing layer, and that the streamwise vorticity persists far into the turbulent region. 22,23,26,27 Evidence for the presence of statistically stationary streamwise vorticity, however, appears to be lacking in all of these spatially-developing mixing layer computations.…”
Section: Introductionmentioning
confidence: 95%
See 4 more Smart Citations
“…24 Whilst these studies were limited to the pre-transition region, more recent research has shown that simulation of initially laminar mixing layers with pseudorandom inflow disturbances leads to post-transition large-scale coherent structures which grow continuously and linearly throughout their lifetimes. 23 Flow visualisation of the high Reynolds number simulated flow shows that streamwise vorticity develops in the mixing layer, and that the streamwise vorticity persists far into the turbulent region. 22,23,26,27 Evidence for the presence of statistically stationary streamwise vorticity, however, appears to be lacking in all of these spatially-developing mixing layer computations.…”
Section: Introductionmentioning
confidence: 95%
“…23 Flow visualisation of the high Reynolds number simulated flow shows that streamwise vorticity develops in the mixing layer, and that the streamwise vorticity persists far into the turbulent region. 22,23,26,27 Evidence for the presence of statistically stationary streamwise vorticity, however, appears to be lacking in all of these spatially-developing mixing layer computations.…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations